Revealing the formation mechanism and band gap tuning of Sb2S3 nanoparticles - Joschko, Maximilian; Fotue Wafo, Franck Yvan; Malsi, Christina; Kisić, Danilo; Validžić, Ivana; Graf, Christina (Beilstein Journal of Nanotechnology, 2021)
Sb2S3 is a promising nanomaterial for application in solar cells and in the fields of electronics and optoelectronics. Herein, Sb2S3 nanoparticles were prepared via the hot-injection approach. In contrast to earlier work, the reaction temperature was decreased to 150 °C so that the reaction was slowed down and could be stopped at defined reaction stages. Thereby, the formation mechanism of the nanomaterial and the associated kinetics could be revealed. Based on morphological and structural analyses, it is suggested that seed particles (type 0) formed immediately after injecting the antimony precursor into the sulfur precursor. These seeds fused to form amorphous nanoparticles (type I) that contained a lower percentage of sulfur than that corresponding to the expected stoichiometric ratio of Sb2S3. The reason for this possibly lies in the formation of an oxygen- or carbon-containing intermediate during the seeding process. Afterward, the type I nanoparticles aggregated into larger amorphous nanoparticles (type II) in a second hierarchical assembly process and formed superordinate structures (type III). This process was followed by the crystallization of these particles and a layer-like growth of the crystalline particles by an Ostwald ripening process at the expense of the amorphous particles. It was demonstrated that the kinetic control of the reaction allowed tuning of the optical band gap of the amorphous nanoparticles in the range of 2.2–2.0 eV. On the contrary, the optical band gap of the crystalline particles decreased to a value of 1.7 eV and remained constant when the reaction progressed. Based on the proposed formation mechanism, future syntheses for Sb2S3 particles can be developed, allowing tuning of the particle properties in a broad range. In this way, the selective use of this material in a wide range of applications will become possible.
Keywords: band gap; kinetics; nanoparticles; Sb2S3; solar cells